Effect of system interface elements' design features and vibration levels on task load and body discomfort in vehicle simulated vibration environments. - Tang, Xing; Yu, Suihuai; Chu, Jianjie; Li, Feilong; Fan, Hao; Jiang, Gang (Work, 2025)
Backgrounds: Touch screens have been extensively utilized in vehicle information systems; however, few studies have centered on the reduction of the touchscreen interaction task load and the increase of body discomfort when driving on unpaved roads. Objective: This study aimed to explore the relationship between the system interface elements' design features and interaction task load in vehicle simulated vibration environments. Method: Using a touch screen computer and E-prime software, we investigated the interaction task load and body parts discomfort of 18 participants in varied vibration frequency environments and interface design elements. Results: The results indicate that vehicle vibration significantly increases system interface interaction task load and causes greater discomfort for the operator. Conclusion: An appropriate increase in the physical size of the interface design features (visual stimulus materials and touch buttons) helps mitigate this negative effect of vibration. The research results can be used as a reference for the current universal design specification of vehicle information system interface in the vibration scenario of unpaved roads.